Changes over 10 years in the retelling of the flashbulb memories of the attack of 11 September 2001. Issue 8 (14th September 2021) - Dégeilh, Fanny; Lecouvey, Grégory; Hirst, William; Heiden, Serge; Pincemin, Bénédicte; Decorde, Matthieu; Meksin, Robert; Eustache, Francis; Peschanski, Denis
ABSTRACT: A flashbulb memory is a highly detailed and vivid autobiographical memory for the circumstances in which one first learned of a surprising, consequential and emotionally arousing event. How retelling of different features of a flashbulb memory changes over time is not totally understood. Moreover, little is known about how the emotional feeling experienced by individuals when they learned about the event modulates these changes. In this study, we explored changes over time in American individuals' retelling of their flashbulb memories of the terrorist attack of 11 September 2001. We conducted textual analysis of 824 testimonies collected from the same 206 individuals 1 week, 11, 25 and again 119 months after the attack. Results showed individuals were more likely to report temporal and emotional details in their retelling early after the event and spatial details in their long-term retelling. In addition, the intensity of emotions felt upon hearing the news about the attack influenced how individuals reported their flashbulb memories over time. Overall, this study provides further support for theories suggesting different rates of forgetting for different canonical features of emotional arousal events.